Anthropogenic influence on rates of aeolian dune activity within the northern European Sand Belt and socio-economic feedbacks over the last ~2500 years. (January 2018) - Lungershausen, Uta; Larsen, Annegret; Bork, Hans-Rudolf; Duttmann, Rainer
In North-Western Europe, Pleistocene sand sheets have been reactivated during phases of Holocene deforestation and agricultural land use. Although there are temporal overlaps between anthropogenic activity and sand sheet reactivation, the root cause and subsequent feedbacks between aeolian activity and societal response remain largely unknown. Here, we seek to establish cause and effect by examining the detailed co-variation in both timing and magnitude of aeolian and anthropogenic activity through the quantification of Holocene dune sediments in combination with archaeological and pollen records. These records indicate a series of complex phases of aeolian activity followed by landscape stabilization, which we attribute primarily to changing patterns of human impact. We find that a steady increase in dune deposition rates in the Medieval Period corresponds to an increase in settlement activity and deforestation (~AD 1000–1500). At their peak, Medieval deposition rates were 3.4 times larger than during the late Pleistocene, the period experiencing the most favourable natural conditions for aeolian sediment transport. Prior to the Medieval Period, relative land-surface stability (represented by a depositional hiatus) persisted from the late Pleistocene until the Roman Iron Age Period (AD 0–400). Deforestation to fuel iron production had minor impact on aeolian activity, as indicated by the lowest recorded deposition rate (0.12 ± 0.02 t/ha/a). Following the Medieval Period peak in deposition rates, aeolian activity diminished rapidly and coincided with the abandonment of nearby human settlement. This sequence of events provides evidence of a direct positive feedback in which Medieval agricultural overexploitation favoured aeolian activity that rendered the landscape practically unworkable for cropping agriculture. Based on our findings and a comprehensive review of Northern European sand belt activity, we interpret a very high sensitivity of aeolian activity to past and present human impact and argue that unsustainable land-use practices have been the cause for widespread settlement abandonment.